ORIGIN OF CHROMITE IN MAFIC-ULTRAMAFIC-HOSTED HYDROTHERMAL MASSIVE SULFIDES FROM THE MAIN URALIAN FAULT, SOUTH URALS, RUSSIA - Tesalina S.G.; Zaykov V.V.; Nimis P.; Augé T. (My University, 2003)
Mafic–ultramafic-hosted hydrothermal Fe–Cu–(Ni–Co) sulfide ores from the Main Uralian Fault Zone (MUFZ), South Urals (Ivanovka and Ishkinino ore fields), contain a relatively large (up to 3%) proportion of chromite. This association is common for magmatic Fe–Ni–Cu sulfides, but definitely unusual for hydrothermal sulfides. Textural, morphological and compositional data are used here to gain an insight into the origin and significance of this unusual chromite–sulfide association. The studied chromites occur both as broken fragments and as euhedral or subhedral crystals, which are included in the sulfides or scattered in their talc±chlorite±saponite±quartz±carbonate matrix. They are characterized by high Cr/(Cr+Al) ratios (0.58–0.85) and range in composition from magnesiochromite to chromite sensu stricto. Textural, morphological and compositional features, as well as the occurrence of relatively high-silica, low-Ti, low-K melt inclusions in some of the crystals, indicate that the ore-associated chromites (i) are a mixed population of grains derived from mafic–ultramafic mantle and crustal magmatic rocks and mantle peridotite melting residua, (ii) have no genetic relation with the host sulfides and (iii) represent relicts derived from the hydrothermally altered country rocks. The compositions of the chromites and of the melt inclusions denote a clear supra-subduction zone signature. The melts parent to the cumulitic chromites had an arc tholeiitic to, possibly, boninitic affinity. These data suggest that the host mafic–ultramafic complexes formed in an early arc or forearc setting and do not represent obducted portions of MORB oceanic lithosphere. Hence, contrary to previous interpretations, the associated massive sulfides could not originate on a mid-ocean ridge, but rather in an early arc or forearc environment. Given the relatively short life of the western Uralian arc system, the most probable time window for sulfide ore deposition is confined to Early to Middle Devonian time.
Keywords: Chromite; South Urals; Main Uralian Fault; VHMS deposits; Ivanovka; Ishkinino